An Update on Hepatorenal Syndrome - Samuel Chan; Kenneth Au; Ross Francis; David W Mudge; David W Johnson; Tony Rahman (Journal of Renal and Hepatic Disorders)
Hepatorenal syndrome (HRS) is one of the many potential causes of acute kidney injury (AKI) in patients with decompensated liver disease. HRS is associated with poor prognosis and represents the end-stage of a sequence of reductions in renal perfusion induced by progressively severe hepatic injury. The pathophysiology of HRS is complex with multiple mechanisms interacting simultaneously, although HRS is primarily characterised by renal vasoconstriction. A recently revised diagnostic criteria and management algorithm for AKI has been developed for patients with cirrhosis, allowing physicians to commence treatment promptly. Vasopressor therapy and other general management, such as antibiotic prophylaxis, need to be initiated whilst patients are assessed for eligibility for transplantation. Liver transplantation remains the treatment of choice for HRS but is limited by organ shortage. Other management options, such as transjugular intrahepatic portosystemic shunt, renal replacement therapy and molecular absorbent recirculating system, may provide short-term benefit for patients not responding to medical therapy whilst awaiting transplantation. Clinicians need to be aware of the pathophysiology and management principles of HRS to provide quality care for patients with multi-organ failure.